Comparison of Warm Compress and Lavender Aromatherapy on Dysmenorrhea in Female Adolescents - Ayuk Naimah; Lailaturohmah (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Dysmenorrhea is a common gynecological problem among female adolescents that affects academic performance, daily activities, and quality of life. Non-pharmacological interventions such as warm compresses and lavender aromatherapy are considered safe and practical alternatives for pain relief. Objectives: This study aimed to compare the effectiveness of warm compresses and lavender aromatherapy in reducing menstrual pain among female adolescents. Methods: A quasi-experimental study with a non-equivalent pretest–posttest control group design was conducted from January to March 2025 at SMK Puspa Bangsa, Banyuwangi. A total of 40 students with a history of dysmenorrhea were selected using proportionate stratified random sampling and divided into two groups: warm compress (n = 20) and lavender aromatherapy (n = 20). Pain intensity was measured before and after the interventions using a validated Numeric Rating Scale. Data were analyzed using paired t-tests for within-group differences and independent t-tests for between-group comparisons. Results: The warm compress group showed a significant reduction in menstrual pain with a greater mean difference than the lavender aromatherapy group. While both interventions were effective, the warm compress group experienced a more pronounced decrease in pain intensity. Independent t-test results confirmed a significant difference in mean pain reduction between the two groups (p-value = 0.000; α<0.05). Conclusions: Warm compresses were more effective than lavender aromatherapy in reducing dysmenorrhea among female adolescents. Warm compresses can be recommended as a simple, safe, and cost-effective non-pharmacological strategy, while lavender aromatherapy may serve as a supportive approach providing relaxation and psychological comfort.